1955
DOI: 10.5962/bhl.title.7264
|View full text |Cite
|
Sign up to set email alerts
|

The cytology and life-history of bacteria

Abstract: acute hepatitis or cirrhosis, this being more common in those cases where the jaundice relapses and convalescence is prolonged.A few cases have also been reported wvhere, after an interval of several years of normal health, clinical cirrhosis has supervened, and, while the evidence that the cirrhosis in these cases is due to antecedent hepatitis is not absolute, it can certainly be considered as highly suggestive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1957
1957
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…This feature was taken advantage of in some ancillary experiments to determine the morphological status of fission as seen under phasecontrast illumination. Organisms a t different stages of development were treated with specific cell-wall stains (see, for example, Bisset, 1955;Tomcsik & Grace 1955); it was found that the time of separation into discrete pieces corresponded approximately to the cell-wall fission-that is, to o-fission, stage (d) of Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…This feature was taken advantage of in some ancillary experiments to determine the morphological status of fission as seen under phasecontrast illumination. Organisms a t different stages of development were treated with specific cell-wall stains (see, for example, Bisset, 1955;Tomcsik & Grace 1955); it was found that the time of separation into discrete pieces corresponded approximately to the cell-wall fission-that is, to o-fission, stage (d) of Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…estimated because acid-Giesma staining (Bisset, 1950) of W organisms reveals 1-4 chromatinic bodies per organism. These low mutation rates are compatible with the fact that under conditions prevailing in continuous culture, W organisms are stable.…”
Section: J N Coetzee and T G Sacksmentioning
confidence: 99%
“…Even the very small swarm cells, with their single polar flagella, are capable of motility in the thin film of moisturg on an agar surface, where normal spirilla are usually completely immobilized. In appearance, these swarmers closely resembled vibrios, and although not strictly variants as in the case of the bacillary branched peritrichously-flagellate or hyphomicrobial forms, they afford further evidence of the ability of spirilla to produce or simulate most of the characters of the bacterial groups to which, on the hypothesis of Bisset (1950Bisset ( , 1955, they may be considered as ancestral. fig.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of bacterial evolution proposed by Bisset (1950) and subsequently elaborated (Bisset, 1955), depends for its validity upon the potentialities of spirilla as forebears of all or most of the main groups of bacteria. The postulated development of different flagellar types from polar-flagellate aquatic ancestors appears to be acceptable to certain workers in this field (Leifson, 1960, p. 18) by whom the theory has been adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation